Analisis Wacana Kritis Konsepsi Relasi Agama dan Negara Hizbut Tahrir Indonesia (Faculty of Communications Science, Dr. Soetomo University, 2017)
One of the political religious organizations whose influence is strong enough is Hizbut Tahrir Indonesia with Islamic Political Discourse Khilafah Islamiyah. The political discourse adopted by Hizb ut-Tahrir certainly reap the controversy in Indonesia whose status is the Unitary State of the Republic of Indonesia which is based on the ideology of Pancasila. Various efforts were made by Hizbut Tahrir Indonesia to enforce its political discourse to penetrate mass communication media such as magazines, tabloids and weekly bulletins. The construction of news in such a way is also always in the sequence as interesting and sepersuasif possible as to influence its readers. Critical discourse analysis is a model of media text analysis that will construct how a medium writes its message, through critical discourse analysis to know the purpose of writing the news. In this study, researchers will construct news content on Al Wa'ie magazine Hizb ut-Tahrir Indonesia especially on the news